The Army and Politics in Indonesia - Crouch, Harold (Book collections on Project MUSE., 2019)
In this highly respected work, Harold Crouch analyzes the role of the Indonesian army in that country's politics, putting special emphasis on the Sukarno years, the gradual take-over of power by the military, and the nature of Suharto's New Order government. The Army and Politics in Indonesia is now available in a paperback edition, updated with a new preface and epilogue that expand the book's coverage to the 1980s.